2011
DOI: 10.1111/j.1369-7625.2011.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a decision aid designed for people facing advanced or terminal illness: a pilot randomized trial

Abstract: Background Patients nearing the end of their lives face an array of difficult decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…Our prior study suggested that inpatients and decision‐makers wanted this PtDA earlier. Our primary care patients validated the main thematic findings from that study stating that the PtDA was highly acceptable and should be given early in the course of illness. What we know now is that near the end of life is likely too late .…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Our prior study suggested that inpatients and decision‐makers wanted this PtDA earlier. Our primary care patients validated the main thematic findings from that study stating that the PtDA was highly acceptable and should be given early in the course of illness. What we know now is that near the end of life is likely too late .…”
Section: Discussionsupporting
confidence: 73%
“…Our primary care patients validated the main thematic findings from that study stating that the PtDA was highly acceptable and should be given early in the course of illness. What we know now is that near the end of life is likely too late . However, whether it should be given during a state of stability by a PCP, or during the time of diagnosis by a specialist or hospital team is unanswered.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations